Optimizing honey production in stingless bee farming - P. Priyambodo; Elly L. Rustiati; Nindy Permatasari; Mahfud Sidik; Indah A. Lestari; Ani A. Yani; Lousanja D. Sa'uddah (Universitas Muhammadiyah Malang, 2023)
Harapan Jaya Village, Way Ratai Subdistrict, Pesawaran Regency has very promising potential for cultivating trigona bees. Lecture and student from University of Lampung team conducted training on stingless bee cultivation in this village in 2022. At the end of 2022, several stingless bee colonies experienced deaths that were allegedly due to lack of nectar sources. This community service activity was carried out to provide understanding and training on vegetation management and adding stingless bee colonies. Activities are carried out with lectures, discussions, and hands-on practice. The results of the activities that have been carried out include the addition of seven types of nectar source plants and two stingless bee colonies. In addition, the community's understanding of the maintenance of stingless bee colonies and their supporting vegetation also increased. This is very supportive of long-term programmed in the achievement of SDGs, especially in the goals of life on land and no poverty.